1988
DOI: 10.1108/eb024714
|View full text |Cite
|
Sign up to set email alerts
|

A Services Marketing Management Model: Integrating Internal and External Marketing Functions

Abstract: In services marketing, the employee plays a central role in attracting, building and maintaining relationships with customers. The recognition of the central role of employees in service marketing has given rise to “internal marketing” programs strongly oriented to employee development. This paper explores the linkage between internal marketing activities (directed at employee recruitment, training, motivation, communication, and retention) and the more traditional external marketing activities (e.g., pricing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 0 publications
0
57
0
4
Order By: Relevance
“…In particular IMO is thought to impact employee attitudes in terms of their satisfaction with their work and motivation to provide good customer service. Tansuhaj et al (1988) and Comm (1989) propose that internal market oriented behaviors on the part of managers lead to higher levels of employee satisfaction and motivation. This is a key tenet of internal marketing, and is based on the assumption that happy and motivated front line employees are essential in the delivery of good service to customers (see for example Sasser and Arbeit, 1976;Berry and Parasuraman, 1991;and Berry 1984).…”
Section: Consequences Of Internal Market Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular IMO is thought to impact employee attitudes in terms of their satisfaction with their work and motivation to provide good customer service. Tansuhaj et al (1988) and Comm (1989) propose that internal market oriented behaviors on the part of managers lead to higher levels of employee satisfaction and motivation. This is a key tenet of internal marketing, and is based on the assumption that happy and motivated front line employees are essential in the delivery of good service to customers (see for example Sasser and Arbeit, 1976;Berry and Parasuraman, 1991;and Berry 1984).…”
Section: Consequences Of Internal Market Orientationmentioning
confidence: 99%
“…Internal marketing is variously seen as involving training (Berry and Parasuraman 1991;Stauss and Schultze 1990); recruitment (Tansuhaj, Randall and McCullough 1988); internal market research (Wasmer and Brunner 1991); internal communications (Piercy 1995); developing job products (Lukas and Maignan 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the findings formerly. (30,31) In addition, we found that Internal marketing perception had a significant positive moderating effect on the relationship between service-ori-…”
Section: Service-oriented Encounter Positively Affects the Patient Samentioning
confidence: 76%
“… The principles of internal marketing are poorly adopted among speed mail services providing firms in Nigeria, thus expected central role of employees in attracting, building and maintaining relationship with customers-Tansuhji, Randall and McCullough (1998), is poor and does not yield desired returns.…”
Section: General Issuesmentioning
confidence: 99%